2020
DOI: 10.1177/1557988320908998
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Metastasis in Elderly Male Bladder Cancer Patients: Potential Risk Factors

Abstract: Bladder cancer is a common type of tumor among elderly male population; it causes intraocular metastasis (IOM). The study investigated the differences between elderly male bladder cancer patients with and without IOM, and identified risk factors for IOM. In this study, 749 elderly male patients (aged ≥50 years) with bladder cancer were included from November 2003 to December 2016. Differences between the IOM and non-IOM (NIOM) groups were evaluated by chi-square test and Student’s t-test. The binary logistic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In contrast, serological tumor markers are widely used in clinical practice, due to their advantages of good reproducibility, low cost, and easy access. To date, a considerable number of researchers have proposed various serological markers related to disease metastasis and prognosis including intraocular metastasis from bladder cancer ; 28 however, there is a lack of specific SI for OM in older adult patients with GC. In our study, we collected serological data from 1165 patients with GC, including: HB, calcium, ALP, TC, TG, HDL, LDL, ApoA1, ApoB, AFP, CA724, CEA, CA199, CA125, CA153, CYFRA21 to 1, and Lp(a) and found that LDL, ApoA1, CA724, and CEA content differed significantly between the OM and NOM groups.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, serological tumor markers are widely used in clinical practice, due to their advantages of good reproducibility, low cost, and easy access. To date, a considerable number of researchers have proposed various serological markers related to disease metastasis and prognosis including intraocular metastasis from bladder cancer ; 28 however, there is a lack of specific SI for OM in older adult patients with GC. In our study, we collected serological data from 1165 patients with GC, including: HB, calcium, ALP, TC, TG, HDL, LDL, ApoA1, ApoB, AFP, CA724, CEA, CA199, CA125, CA153, CYFRA21 to 1, and Lp(a) and found that LDL, ApoA1, CA724, and CEA content differed significantly between the OM and NOM groups.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 Therefore, in recent years, macromolecule materials have been used in the delivery of CpG ODN, including graphene oxidechitosan nanocomposites 36 and N-isopropylacrylamidemodified polyethyleneimine (PEN). 37 Previous studies demonstrated that the N-Ac-L-Leu-PEI/CpG ODN 2006 complex (w: w = 1: 1) was superior to microRNAs and single-stranded oligo DNAs (w: w = 2:1) 22,23,38 and to plasmid DNA (w:w = 0.6-0.8:1). 24 The PEN vehicle could completely retard ODN MT01 at a mass ratio of 0.5.…”
Section: Discussionmentioning
confidence: 99%
“…N-Ac-L-Leu-PEI significantly improved the biocompatibility and transfection efficiency, and significantly decreased protein adsorption and hemolytic activity of the PEI25K matrix. This vehicle has been successfully used to deliver the p53 gene, 21 a DNAzyme 22 and microRNA 23,24 to trigger the pronounced suppression of tumor cells and to upregulate bone formation in vivo and in vitro.…”
Section: Introductionmentioning
confidence: 99%